Evaluation of Bartın river water quality index and suitability as irrigation water with physicochemical parameters - Güneş, Gülten; Güneş, Gülten (Yildiz Technical University, 2022)
In this study, it was aimed to determine the water quality of Bartın River and its usability as irrigation water. In order to evaluate the change of water quality according to the precipitation the samples were collected from 4 points in December and July months. pH, NO3, SO4, Cl-, total phosphorus (TP), chemical oxygen demand (COD), suspended solid (SS), turbidity, some cations and metals were analyzed in the collected samples. The assessment of physicochemical parameters was made according to the Surface Water Quality Regulation. It was determined that SS and turbidity parameters increased after precipitation and 98% of turbidity was caused by SS. Cl-, Na+, K+, Ca+2, Mg+2, SO4-2, TP were determined higher in the dry period. Although COD, total dissolved solid (TDS), electrical conductivity (EC), NO3 were higher in the rainy season, the difference between the two periods is not much. According to the water quality index, water quality was poor at all sampling points during the rainy season. In the dry period, good quality was also determined at only 1 sampling point. COD is the parameter with the greatest effect on effective weight and water quality. Irrigation water suitability was evaluated with the indexes sodium adsorption ratio (SAR), (EC), %Na, magnesium ratio (MR), Kelly index (KI), potential salinity (PS) and total hardness (TH). River water is suitable as irrigation water in both periods according to SAR, %Na, MR, KI indexes. However, since the potential salinity (PS) value is greater than 3 µeq/L at the SP4 in the dry period, it is not suitable as irrigation water. Its total hardness value is >180 mg/L, so it is in the very hard water class. © 2022 Elsevier B.V., All rights reserved.
Evaluation of Bartın river water quality index and suitability as irrigation water with physicochemical parameters
Keywords: Bartın River; Irrigation Water Quality; Kelly Index; Sodium Adsorption Ratio; Water Quality Index